Pastoral Konseling dalam Budaya Marrenggan’nu Rumarrada’a - Awalo, Merry L; Brek, Ivane Dear Suryani (PADAMARA: Jurnal Psikologi dan Sosial Budaya, 2024)
Talaud culture is an integral part of Indonesian culture which has a wide cultural diversity. The Talaud Islands Regency, located in North Sulawesi Province, has a rich and unique culture, which continues to be preserved as the local wisdom of the local community. The Talaud community had cultural values before the gospel entered the land of Porodisa (Talaud), one of which is the Marrengan'nu Rumarada'a Culture which in Indonesian can be interpreted as providing support to the sick who do not heal in the form of a prayer request to God to ask for healing. With the understanding that the pain experienced is the result of resentment and sins committed in the past, it is necessary to make an effort to marrengan'nu rumarada'a which contains the values of togetherness, mutual cooperation, and concern for others. The traditional elders (Ratum banua and inanggu wanua) will play a very important role in this event with expressions or sentences in Talaud